Therapeutic Potential for Targeting the Suppressor of Cytokine Signalling‐1 Pathway for the Treatment of SLE. (26th October 2016) - Sukka‐Ganesh, B.; Larkin, J.
Abstract: Although the specific events dictating systemic lupus erythematosus (SLE) pathology remain unclear, abundant evidence indicates a critical role for dysregulated cytokine signalling in disease progression. Notably, the suppressor of cytokine signalling (SOCS) family of intracellular proteins, in particular the kinase inhibitory region (KIR) bearing SOCS1 and SOCS3, plays a critical role in regulating cytokine signalling. To assess a relationship between SOCS1/SOCS3 expression and SLE, the goals of this study were to (1) evaluate the time kinetics of SOCS1/SOCS3 message and protein expression based on SLE‐associated stimulations, (2) compare levels of SOCS1 and SOCS3 present in SLE patients and healthy controls by message and protein, (3) relate SOCS1/SOCS3 expression to inflammatory markers in SLE patients and (4) correlate SOCS1/SOCS3 levels to current treatments. We found that SOCS1 and SOCS3 were most abundant in murine splenic samples at 48 h subsequent to stimulation by anti‐CD3, LPS or interferon‐gamma. In addition, significant reductions in SOCS1 and SOCS3 were present within PMBCs of SLE patients compared to controls by both mRNA and protein expression. We also found that decreased levels of SOCS1 in SLE patients were correlated with enhanced levels of inflammatory markers and upregulated expression of MHC class II. Finally, we show that patients receiving steroid treatment possessed higher levels SOCS1 compared to SLE patient counterparts and that steroid administration to human PBMCs upregulated SOCS1 message in a dose‐ and time‐dependent manner. Together, these results suggest that therapeutic strategies focused on SOCS1 signalling may have efficacy in the treatment of SLE.